Egy szlavóniai nagybirtok gazdasági vonatkozásai : 18-19. század - Kaposi, Zoltán (Közép-Európai Közlemények, 2013)
In this study I am dealing with the economic and regional changes of the Ludbreg Estate (beyond the Drava River), belonging to the Batthyány Entail. This large estate was located in an area which had a part usually flooded several times in a year due to three rivers. Therefore, till the Dual Monarchy husbandry (livestock, fishery) had a highly important role both in the manorial and serfs’ husbandry. In 1860s and 1870s the railway turned up which significantly improved the possibility of transportation. In the last third of the century wheat production became more important. High prices of grain urged the transformation of the area. Deforestation started, instead of them grain fields were created. More and more lands were recaptured from the rivers. The three manors (21.27 km2) which were leased out generated high profit to Prince Batthyány until the World War I. The economic boom came to an end in 1918. After the World War I the Ludbreg Estate became the territory of the newly born South Slavic state. A part of it was parcelled while Prince László Batthyány managed to sell the remaining.